The effect of disinfectants on the accuracy, quality and surface structure of impression materials and gypsum casts: A comparative study using light microscopy, scanning electron microscopy and micro computed tomography - Vrbova, Radka; Bradna, Pavel; Bartos, Martin; Roubickova, Adela (Dental materials journal, 2020)
The aim of this study was to compare the effect of several commercially available disinfectants on the accuracy of various types of impression materials and their compatibility with gypsum including surface quality and structure evaluation. Four alginate and three elastomeric impression materials in combination with disinfectants Aseptoprint Liquid, Zeta 7 solution, Silosept and Dentaclean Form were tested. The dimensional changes, detail reproduction, the compatibility with gypsum and surface/subsurface morphology were evaluated using light microscopy, scanning electron microscopy and micro computed tomography. Two alginate materials disinfected in Dentaclean Form exhibited the most significant differences (p<0.0001). The loss of detail on some alginate impressions in combination with this disinfectant including deterioration and change of morphology of gypsum surfaces was observed. Porosity in subsurface area and exposed large particles were detected. It was confirmed that the desired properties of impressions may be negatively affected in combination with some disinfectants.
Keywords: zubní modely; testování materiálů; Disinfectants; povrchové vlastnosti; Dental Impression Materials; síran vápenatý; Dental Disinfectants; mikroskopie elektronová rastrovací; Calcium Sulfate; Materials Testing; X-Ray Microtomography; rentgenová mikrotomografie; Microscopy, Electron, Scanning; Surface Properties; zubní dezinficiencia; dezinficiencia; Models, Dental; materiály pro zubní otisky